Modeling and simulation of grid-connected solar photovoltaic systems with D-statcom and dvr to improve stability in distribution system - Abd. Rashid, Hana Munirah (2021)
Electrical utilities face problems such as the rising cost of electricity, aging equipment, increasing demand for electricity, regulating frequency, and the difficulties of incorporating renewables into the grid. The accumulated global photovoltaic (PV) particularly the installation of Grid-Connected Solar Photovoltaic (GCPV) systems has been exponentially expanding around the world. However, as the PV penetration and global PV market have recently grown, there are challenges to the utility companies regarding the power quality and the reliability of the system. This is because the integration of power electronics has raised concerns about the safe operation and protection of the equipment. Hence, the feasible solution to solve these problems is installing Distributed Flexible AC Transmission System (D-FACTS) devices to the distribution grid through the point of common coupling (PCC). The purpose of this project is to model and simulate 100 kW and 250 kW solar PV systems that are connected to the utility distribution system with and without Distribution Static Synchronous Compensator (D-STATCOM) and Dynamic Voltage Restorer (DVR) under normal and faults condition in MATLAB/ Simulink. The test systems consist of a PV array that is connected in series and parallel modules, a DC-DC Boost Converter, Maximum Power Point Tracking (MPPT) control, DC-AC inverter, inverter control, filter, three-phase load, distribution transformer, and grid equipment. The grid operates test systems I and II at the nominal three-phase line to line voltage of 260 V, supplied from 100 kVA and 250 kVA 25/ 0.26 kV distribution transformer. The test system I and II are tested with the Perturb and Observe technique. The simulation results showed that the installation of D-STATCOM and DVR in GCPV systems improved 80-90% of the output power from the PV systems, and stabilized the level of the RMS voltage and current within 5% of its nominal value at the distribution feeder under normal and fault conditions. The implementation of D-FACTS devices in GCPV systems will be beneficial for future power system stability studies in the distribution system